Effects of Botulinum Toxin A on the Blood Flow in Expanded Rat Skin. Issue 5 (4th May 2022) - Liu, Hengxin; Yu, Zhou; Wang, Jiayang; Zhang, Xi; Lei, Lei; Zhang, Yu; Su, Yingjun; Ma, Xianjie
Abstract: Background Poor blood supply can easily lead to expander extrusion and necrosis at the distal expanded flap. Botulinum toxin A (BTX-A) has been previously found to improve pedicled flap blood flow perfusion, but its effects on the blood supply of expanded skin remain unclear. Therefore, this study aimed to evaluate the effects of BTX-A on blood flow perfusion during and after expansion. Methods Eighteen Sprague-Dawley rats were randomly divided into a BTX-A group and a control group. BTX-A or normal saline was injected intradermally into the marked skin on the back immediately. Then expanders were implanted in the rats. One week later, inflation of the expander with normal saline was started and performed twice a week to reach an intracapsular pressure of 8 kPa. The skin blood flow was measured before each injection. After 4 weeks of expansion, the sample was harvested for histological staining to measure the diameter and density of blood vessels; meanwhile, a 2 cm× 8 cm expanded random flap was elevated and sutured in situ . Blood flow perfusion and flap survival were observed. Results Compared with the control group, the BTX-A group had more blood flow, a larger blood vessel diameter, and higher blood vessel density in the expanded skin. Additionally, the flap of the BTX-A group had good blood flow perfusion and a high proportion of flap survival area within 7 days after expanded flap transfer. Data were analyzed using an independent t-test. Conclusion Pre-surgical BTX-A treatment may increase angiogenesis and vasodilatation, with subsequent blood perfusion elevation during and after expansion, and obtain a greater proportion of survival area of the transferred expanded flap.